2013
DOI: 10.1177/1933719112451147
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Remodeling and Nonendometrium-Like Menstrual Cycling Are Hallmarks of Peritoneal Endometriosis Lesions

Abstract: We identified differentially expressed genes comparing peritoneal endometriosis lesions (n ¼ 18), eutopic endometrium (n ¼ 17), and peritoneum (n ¼ 22) from the same patients with complete menstrual cycles using microarrays (54 675 probe sets) and immunohistochemistry. Peritoneal lesions and peritoneum demonstrated 3901 and 4973 significantly differentially expressed genes compared to eutopic endometrium, respectively. Peritoneal lesions significantly revealed no correlation with a specific menstrual cycle pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 66 publications
0
10
1
Order By: Relevance
“…This has been supported by a morphometric study showing that tight junctions were missing or disrupted in endometrioma compared to eutopic endometrium [39]. In a more recent study, microarray analyses revealed an upregulation of transcripts of JAM-B and JAM-C and of claudin-1, -5 and -11 and a downregulation of ZO-3, occludin and claudin-3, -4 and -7 in peritoneal endometriotic lesions compared to the corresponding eutopic endometrium [104]. However, these observations were not validated by PCR or immunohistochemical staining.…”
Section: Direct Cell–cell Interactions In Endometrial Pathophysiologymentioning
confidence: 76%
“…This has been supported by a morphometric study showing that tight junctions were missing or disrupted in endometrioma compared to eutopic endometrium [39]. In a more recent study, microarray analyses revealed an upregulation of transcripts of JAM-B and JAM-C and of claudin-1, -5 and -11 and a downregulation of ZO-3, occludin and claudin-3, -4 and -7 in peritoneal endometriotic lesions compared to the corresponding eutopic endometrium [104]. However, these observations were not validated by PCR or immunohistochemical staining.…”
Section: Direct Cell–cell Interactions In Endometrial Pathophysiologymentioning
confidence: 76%
“…Estrogen and progesterone play an important role in the development and maintenance of endometriosis. Although endometriotic cells do not have high proliferative activity, supported by Ki67 studies and cell cycle gene expression, stimulation through steroid hormones along with growth factors promotes steady and slow growth [ 43 45 ]. Additionally in a mouse model stimulation with estrogen led to an increase of MMP2 and promoted ectopic implantation of endometrial tissue [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To identify co-expressed mRNAs that were differentially expressed lncRNAs and lncRNA in endometriosis, the raw CEL files for GSE7305 (10 normal samples and 10 endometriosis samples) ( 18 ), GSE7846 (5 normal samples and 5 endometriosis samples) ( 19 ) and GSE29981 (20 endometriosis samples) were downloaded from GEO ( ), and E-MTAB-694 (17 normal samples and 18 endometriosis samples) ( 20 ) from ArrayExpress ( ). The limma and Affy packages were used to read and process the raw CEL files.…”
Section: Methodsmentioning
confidence: 99%